2011
DOI: 10.4236/ijoc.2011.12004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Biodiesel Fuel Production Using Novel Fibrous Catalyst Synthesized by Radiation-Induced Graft Polymerization

Abstract: An efficient fibrous catalyst for the biodiesel fuel production has been synthesized by radiation-induced graft polymerization of 4-chloromethylstyrene onto a nonwoven polyethylene (NWPE) fabric followed by amination with trimethylamine (TMA) and further treatment with NaOH. The degree of grafting of NWPE fabric and TMA group density of fibrous catalyst could easily and reproducibly be controlled within a range of up to 340% and 3.6 mmol-TMA/g-catalyst, respectively. In the transesterification of triglycerides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The amidoxime fabric adsorbent was obtained by treatment of the AN/MAA-grafted fabric with a hydroxylamine solution [36,37], that is, the AN/MAA-grafted fabric was immersed in a 3.0 wt % hydroxylamine solution (pH 7.0 adjusted by KOH) at 80 °C for more than 15 min. Under this condition, it was confirmed that all of the cyanide (CN) groups on the graft chains were converted into amidoxime (C(NH 2 )=NOH) groups [36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amidoxime fabric adsorbent was obtained by treatment of the AN/MAA-grafted fabric with a hydroxylamine solution [36,37], that is, the AN/MAA-grafted fabric was immersed in a 3.0 wt % hydroxylamine solution (pH 7.0 adjusted by KOH) at 80 °C for more than 15 min. Under this condition, it was confirmed that all of the cyanide (CN) groups on the graft chains were converted into amidoxime (C(NH 2 )=NOH) groups [36].…”
Section: Methodsmentioning
confidence: 99%
“…The irradiated fabric was then immersed in an oxygen-free monomer solution at the designed temperature for grafting, under which the polymeric radicals initiated the graft polymerization. In this work, an amidoxime fabric adsorbent was synthesized by co-grafting of acrylonitrile (AN) and methacrylic acid (MAA) and subsequent amidoximation with hydroxylamine [36,37], while an ammonium fabric adsorbent was synthesized by grafting of chloromethylstyrene (CMS) and subsequent quaternization with trimethylamine [38]. The chromium removal of the resultant fabric adsorbents was tested in batch and column modes.…”
Section: Introductionmentioning
confidence: 99%
“…Grafted fibrous catalyst for BDF production was synthesized by radiation-induced emulsion grafting technique, as published previously [18]. PE/PP nonwoven fabric was irradiated with electron beam (100 kGy).…”
Section: Synthesis Of Grafted Fibrous Catalyst For Biodiesel Fuel Promentioning
confidence: 99%
“…The catalytic performance of the grafted fibrous catalyst was evaluated by the transesterification of TG and alcohols under the following standard conditions, as published previously [18]. The transesterification tests were performed in a batch reactor equipped with a magnetic stirrer.…”
Section: Transesterification Procedures With Grafted Fibrous Catalystmentioning
confidence: 99%
“…The potential of application of fibrous basic catalyst prepared by radiation induced grafting (RIG) of vinylbenzyl chloride onto polyethylene (PE) nonwoven sheet followed by amination for transesterification of triolein with various types of alcohols was investigated [9] [10]. Similar radiation grafted and aminated catalyst based on PE/polypropylene (PE/PP) nonwoven sheet was evaluated for transesterification of triacetine [11].…”
Section: Introductionmentioning
confidence: 99%